Pendidikan Islam Rahmat li al-‘Alamin dan Implikasinya terhadap Karakter (Studi Pesantren Metal Mulim al-Hidayah Pasuruan) - Noor, Aditia Muhammad (Jurnal Penelitian Pendidikan Islam, 2021)
The “Metal” Islamic boarding school was established with a very humanistic purpose. While some educational institutions only accommodate students excelers, superior, smart and have character. The “Metal” person boarding school is present as a place that accommodates students with various social backgrounds, ranging from druging addicts, homeless people, free sex victims, until toddlers who deliberately abandoned their parents. Seeing the arrogance and inequality of education while this time, making the “Metal” person boarding school take a very meaningful role for them to be formed into people who have character. Because education is the right of all humans without having to look at the status of his past. Rahmatan li al-'alamin Islamic education in the “Metal” person boarding school have an impact on the character of students who are able to make them as perfect people.